Bending and vibrational behaviors of piezoelectric nonlocal nanobeam including surface elasticity. Issue 2 (3rd April 2019) - Eltaher, M. A.; Omar, Fatema-Alzahraa; Abdalla, W. S.; Gad, E. H.
ABSTRACT: This manuscript illustrates coupled effects of nonlocal elasticity and surface properties on static and vibration characteristics of piezoelectric nanobeams using thin beam theory. The mechanical and piezoelectric surface nanoscale properties are governed by Gurtin–Murdoch model. The length scale effect is imposed to the problem by including nonlocal elasticity theory to describe the long–range atoms interactions. The governing equations are derived by Hamilton's principle and solved numerically using the finite-element method. The proposed model is verified and validated with previous published works. Numerical results illustrate the effects of nonlocal parameter, surface elasticity, and boundary conditions on the bending and dynamic characteristics of the nanobeam. It is found that, the nonlocal effect and the surface piezoelectricity effect play a significant role on the static deflection and the natural frequencies. The obtained results are in good agreement with previous published works. This study should have useful insights on the design, fabrication and applications of piezoelectric-beam-based nanodevices.